Relationship between Remittances and Inflation in Nepal - Dahal, Kiran; Chaudhary, Arbind; Adhikari, Naveen; Bista, Nawaraj (Journal of Development and Administrative Studies, 2019)
Empirical evidence highlights the significant impact of remittances on a country’s macroeconomic indicators. This holds particular significance for import-dependent developing nations like Nepal, where remittances serve as a crucial source of foreign currency earnings and facilitate the financing of imports. However, there remains a limited understanding of their implications for inflation, as their effects on inflation are contingent upon whether the demand or supply side is more influenced by remittances. This study leverages time series data and employs an error correction model (ECM) to explore the influence of remittances on the domestic price level. The findings indicate that the inflow of remittances has a dampening effect on the domestic inflation rate. This suggests that remittances have played a pivotal role in enabling the import of relatively more affordable goods from abroad, notwithstanding their impact on the overall expenditure of the economy. Furthermore, our research reveals that conventional macroeconomic indicators such as GDP, narrow money supply, and Indian inflation appear to exert pressure on domestic inflation in Nepal. These findings offer valuable insights into the complex relationship between remittances and inflation dynamics in the Nepalese context.